An examination of ideology in translation via modality: Wild Swans and Mao's Last Dancer. (4th May 2017) - Li, Long
ABSTRACT: This paper compares the semantics of grammatical choices in Chinese with the system ofmodality in English, with particular reference to descriptions from systemic functional linguistics. The latter is a theory much informed by both English and Chinese in its development. Based on existing literature on language typology, this paper seeks not only an examination of the usefulness of this grammatical potential to translation scholars but also to provide more delicate typological descriptions to ensure commensurability in translation. As modality is often expected to be a key site for expressing interpersonal judgements, this paper investigates whether choices in this system can be indicative of patterns of ideologically motivated regularities, or shifts, in the translated texts. This paper uses the Chinese translations of Wild Swans and Mao's Last Dancer as domains of study, both of which are highly successful but politically controversial autobiographies written in English by Chinese migrant writers. Incorporating both quantitative and qualitative approaches, this study has found how meaningful choices of modality have altered the evaluation of political leaders.